Adipocytokines and Associations With Abnormal Body Composition in Rheumatoid Arthritis. Issue 3 (31st October 2022) - Baker, Joshua F.; Katz, Patricia; Weber, David R.; Gould, Patrick; George, Michael D.; Long, Jin; Zemel, Babette S.; Giles, Jon T.
Abstract : Objective: We determined associations between adipokines and abnormal body composition in patients with rheumatoid arthritis (RA). Methods: Combining data from three RA cohorts, whole‐body dual‐energy absorptiometry measures of appendicular lean mass and fat mass indices were converted to age‐, sex‐, and race‐ and ethnicity‐specific Z scores. Lean mass relative to fat mass was determined based on prior methods. Independent associations between body composition profiles and circulating levels of adiponectin, leptin, and fibroblast growth factor (FGF)‐21 were assessed using linear and logistic regression models adjusting for demographic characteristics and study cohort. We also determined the improvement in the area under the curve (AUC) for prediction of low lean mass when adipokines were added to predictive models that included clinical factors such as demographic characteristics, study, and body mass index (BMI). Results: Among 419 participants, older age was associated with higher levels of all adipokines, whereas higher C‐reactive protein level was associated with lower adiponectin levels and higher FGF‐21 levels. Greater fat mass was strongly associated with lower adiponectin levels and higher leptin and FGF‐21 levels. Higher levels of adiponectin, leptin, and FGF‐21 were independently associated with low lean mass. The addition of adiponectin and leptin levels to regression models improved prediction of low lean mass when combined with demographic characteristics, study, and BMI (AUC 0.75 vs. 0.66). Conclusion: Adipokines are associated with both excess adiposity and low lean mass in patients with RA. Improvements in the prediction of body composition abnormalities suggest that laboratory screening could help identify patients with altered body composition who may be at greater risk of adverse outcomes.